Antihyperurisemic Activity of Aqueous Celery Infusion by Xanthine Oxidase Enzyme Inhibition - Atiqoh Zummah; Rahma Diyan Martha (Majalah Obat Tradisional, 2018)
Hyperuricemia is a metabolic disorder because of excessive uric acid production. The high prevalence of hyperuresemia in the world, especially in Indonesia makes the research of antihyperurisemia drugs very needed today. The purpose of this study was to determine the activity of water infusion extract from celery stems and leaves to inhibited xanthine oxidase enzyme. Xanthine oxidase enzyme plays a role in change of hypoxanthine to xanthine and then becomes uric acid. The activity of xanthine oxidase enzyme was determined by UV spectrophotometry method and using xanthine substrate. Absorption at 290 nm indicates the presence of a uric acid product from xanthine oxidation by the xanthine oxidase enzyme. Infused extract which has the smallest absorption at 290 nm showed a better inhibitory ability of the xanthine oxidase enzyme because the change of xanthine substrate to uric acid is inhibited. The result showed the celery stems water infusion extract had better inhibition activity than celery leaves water infusion extract. The best inhibition percentage of celery stems water infusion was 90,25%, while the celery leaves water infusion was 69.07% both of at 20% concentration. The type inhibition of celery stems water infusion extract to xanthine oxidase enzyme showed an uncompetitive inhibition type because showed change in Km and Vmax values. Km and Vmax values before the addition of water infusion of celery stems were 104.33 ppm and 3.83 U/mL respectively changed to 74.49 ppm and 2.69 U/mL after the addition of extract.